(untitled) (Comprehensive Journal of Science, 2026)
This preliminary study connduted in Libya aimed to investigate the effect of the alcoholic extract of Peganum harmala seeds on the kidney tissue of adult male albino rabbits , the animals were divided into groups and treated with different concentrations of the extract , the results showed highly significant differences between the groups (P<o.oo1) across all measured histomorphometric parametric parameters , the group treated with 30% extract exhibited clear histological changes , including vascular congestion and a marked increase in glomerular size compared to the control group , in contrast, the group treated with 10% extract showed only mild structural alterations .